Sound recordings of leading professors of Spanish Manufacturing Engineering. Analysis of contents. - Sevilla-Hurtado, Lorenzo; Claver Gil, Juan; Sebastián Pérez, Miguel Ángel (Sociedad de Ingeniería de Fabricación / Cintia Barajas, Jesús Caja, Roque Calvo, Piera Maresca, Teresa Palacios, 2019)
"Academic Lives in Industrial Engineering" is one of the different initiatives developed by PATRIF, a Working Group of the Manufacturing Engineering Society (MES) / Sociedad de Ingeniería de Fabricación (SIF). This activity intends to create a sound recording archive with interview format, in order to disseminate the trajectory of the great professors of the Spanish Industrial Engineers Faculties. It seeks to preserve and bring closer to the new generations the experiences and the personality of these professors, with a story told in the first person. This work aims to show the characteristics of this activity, presenting the profile of the interviewees, pointing out the most outstanding aspects of their interventions, carrying out an analysis of the follow-up of the broadcasted interviews and assessing their impact. Despite other areas of engineering are covered in this initiative, present work limit its analysis to the group of professors who have developed their academic and professional life within the Manufacturing Engineering and it also wants to serve as tribute and recognition to their trajectories and dedication to the Spanish Manufacturing Engineering.
ISBN 978-84-09-10387-4
Keywords: Industria; Industrial heritage; academic life; manufacturing engineering; PATRIF; SIF-MES